Structural stability of a golden semiconducting orthorhombic polymorph of Ti2O3 under high pressures and high temperatures - Ovsyannikov, Sergey; Wu, Xiang; Shchennikov, Vladimir V.; Karkin, Alexander E.; Dubrovinskaia, Natalia; Garbarino, Gaston; Dubrovinsky, Leonid (Journal of physics. Condensed matter, 2010)
An orthorhombic polymorph of titanium oxide (Ti2O3) has been synthesized at high pressure-high temperature (HP-HT) conditions. It has been refined in the Pnma space group and the Th2S3 structural type with the unit cell parameters as follows: a = 7.8248(6) Å, b = 2.8507(4) Å, c = 8.0967(3) Å, V = 180.61(1) Å3 and Z = 4. The samples of Pnma-Ti2O3 were of a golden colour, in contrast to the conventional black corundum-structured Ti2O3. The structural stability of this polymorph has been examined by simultaneous Raman and x-ray diffraction studies under high pressure over 70 GPa and high temperature over 2200 K. No phase transformations or chemical reactions have been established. The electrical resistivity of Th2S3-structured Ti2O3 samples showed a semiconducting behaviour and, at ambient conditions, was equal to 0.20-0.46 Ω cm. Conventional near-infrared absorption spectroscopy established the absence of energy gaps above 0.25 eV.